Greater hippocampal volume is associated with PTSD treatment response. (30th June 2016) - Rubin, Mikael; Shvil, Erel; Papini, Santiago; Chhetry, Binod T.; Helpman, Liat; Markowitz, John C.; Mann, J. John; Neria, Yuval
Abstract: Previous research associates smaller hippocampal volume with posttraumatic stress disorder (PTSD). It is unclear, however, whether treatment affects hippocampal volume or vice versa . Seventy-six subjects, 40 PTSD patients and 36 matched trauma-exposed healthy resilient controls, underwent clinical assessments and magnetic resonance imaging (MRI) at baseline, and 10 weeks later, during which PTSD patients completed ten weeks of Prolonged Exposure (PE) treatment. The resilient controls and treatment responders (n=23) had greater baseline hippocampal volume than treatment non-responders (n=17) ( p =0.012 and p =0.050, respectively), perhaps due to more robust fear-extinction capacity in both the initial phase after exposure to trauma and during treatment. Highlights: PTSD patients responsive to prolonged exposure (PE) treatment and trauma-exposed resilient controls had greater hippocampal volume than treatment non-responders. These findings support the notion that the hippocampus is key to contextual modulation of fear extinction, which is necessary for accurately distinguishing between contextual cues that signal safety and those that signal threat. The study found no significant association between symptomatic improvement following PE and change in hippocampal volume.